Anomalous interarterial right coronary artery culprit vessel in ST-segment elevation myocardial infarction. Issue 2 (March 2022) - Nikolakopoulos, Ilias; Lopes, Bernardo B. C.; Vemmou, Evangelia; Karacsonyi, Judit; Cavalcante, João; Lesser, John; Brilakis, Emmanouil S.
Abstract : Supplemental Digital Content is available in the text.